Challenging conformity: A case for diversity - Willemien Kets; Alvaro Sandroni (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2015)
Why do diverse groups outperform homogeneous groups in some settings, but not in others? We show that while diverse groups experience more frictions than homogeneous ones, they are also less conformist. Homogeneous groups minimize the risk of miscoordination, but they may get stuck in an ineffcient equilibrium. Diverse groups may fail to coordinate, but if they do, they tend to attain effciency. This fundamental tradeoff determines how the optimal level of diversity varies with social and economic factors. When it is vitally important to avoid miscoordination, homogeneous groups are optimal. However, when it is critical to implement new and effcient practices, diverse groups perform better.
Keywords: 330